HEMATOLOGICAL PARAMETERS IN THE IDENTIFICATION AND CLASSIFICATION OF ANEMIAS (CIPEEX, 2025)
Hemoglobin is a fundamental protein for life, responsible for carrying oxygen from the lungs to thetissues. The World Health Organization (WHO) defines anemia as the condition in whichhemoglobin levels are below normal, often caused by a lack of nutrients such as iron, zinc, vitaminB12, and proteins. When hemoglobin decreases, the body attempts to adapt by redirecting blood tovital organs and increasing cardiac output. However, these mechanisms are not always sufficient,especially in more vulnerable individuals. The most common symptoms of iron-deficiency anemiaare apathy, fatigue, weakness, and pallor of the skin and mucous membranes, which may worsenover time and further compromise energy and well-being. In general, anemias can be classifiedaccording to the duration (acute or chronic), the main cause (reduced red blood cell production,increased destruction, or blood loss), and also by hematimetric indices from the complete bloodcount (normocytic/normochromic, macrocytic, or microcytic/hypochromic). These parameters helphealth professionals investigate, diagnose, and monitor the patient’s clinical progress. The analysisof hematological indicators obtained from blood tests aims to identify, differentiate, and monitor theprogression of different types of anemia and other hematological diseases. This summaryencompasses selected studies analyzed to understand the diagnosis, classification, and monitoringof anemias. It is a literature review based on data collected from databases such as GoogleScholar, covering publications from the last five years. The review indicates that the laboratorydiagnosis of anemia begins with the interpretation of parameters provided by the complete bloodcount, especially those related to the red blood cell series (erythrogram). Among the main indicesevaluated are hemoglobin concentration (Hb), the percentage of red blood cells relative to totalblood volume (hematocrit or Ht), the total red blood cell count (RBC), and reticulocyte count.Erythrocyte analysis through the complete blood count provides essential information onhematimetric indices, allowing assessment of the patient’s hematological status. These parametersalso include the mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), meancorpuscular hemoglobin concentration (MCHC), and red cell distribution width (RDW), as well asmorphological evaluation of red blood cells. From this perspective, the complete blood count is themain blood analysis tool, essential for the differentiation, diagnosis, and monitoring of anemicconditions. It allows tracking the progress of treatment, whether pharmacological or not, and is alsocrucial for early diagnosis and monitoring of diseases such as infections and leukemias, as well asfor routine evaluations, preoperative assessments, and monitoring of various health treatments.
Keywords: Anemia; Complete Blood Coun; Hematimetric Indices